Chitosan/Bentonite Composite Membrane Doped with LiOH as an Electrolyte Candidate for Energy Storage Systems - Sri Hilma Siregar; Akmilna Aqlina Manurung; Meidita Kemala Sari; Hasmalina Nasution (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
This study aimed to synthesize and characterize chitosan/poly(vinyl alcohol) (PVA)-based polymer electrolyte membranes modified with bentonite and LiOH using the solvent casting method. The chitosan:PVA composition was varied from 10:90 to 90:10 to evaluate its effects on the physical, mechanical, thermal, morphological, and electrochemical properties of the membranes. Characterization was conducted through thickness, tensile strength, and porosity measurements, as well as Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy–Energy Dispersive X-ray Spectroscopy (SEM–EDX), Thermogravimetric Analysis–Derivative Thermogravimetry (TGA–DTG), and Cyclic Voltammetry (CV). The results showed that the membrane with a chitosan:PVA ratio of 10:90 exhibited the highest tensile strength of 19.86 MPa, whereas the membrane with a ratio of 30:70 achieved the highest porosity of 20.49%, which facilitated ion transport and enhanced electrochemical performance. FTIR analysis confirmed intermolecular interactions among chitosan, PVA, bentonite, and LiOH through the O–H, N–H, C=O, Si–O, and Li–O functional groups. SEM–EDX analysis revealed that carbon and oxygen were the predominant elements, while calcium, sodium, silicon, and lithium were also detected, consistent with the membrane composition. Cyclic voltammetry demonstrated typical capacitive behavior, with the current response increasing as the scan rate increased. Meanwhile, TGA–DTG analysis indicated gradual thermal degradation, with the primary decomposition occurring between 350°C and 550°C, demonstrating good thermal stability. Overall, the chitosan/PVA–bentonite composite membrane doped with LiOH shows strong potential as an environmentally friendly polymer electrolyte membrane for energy storage applications, particularly lithium-ion batteries.